PENGARUH KECERDASAN EMOSIONAL TERHADAP PERILAKU MENYIMPANG REMAJA DI DESA SILAM KECAMATAN KUOK KABUPATEN KAMPAR - muhammad ilyas ilyas; Dea Nurul Azizah (Universitas Islam Ahmad Dahlan, 2020)
This study discusses emotional intelligence for adolescents in Silam Village, Kuok Subdistrict, Kampar District. The purpose of this study was to study how emotional intelligence on families in Silam Village, Kuok District, Kampar District. The type of research used is descriptive quantitative research. The population subjects were 250 teenagers in Silam Village and a sample of 71 adolescent Cluster Random Sampling. The technique of collecting data using a questionnaire with a Likert scale. The data analysis technique in this study was carried out by simple linear regression analysis, and the processing in this study used the SPSS version 17.0 (Statistical Products and Services Solution) program for windows. The results showed a significant influence between emotional intelligence on adolescent behavior in the Silam Village, Kuok Subdistrict, Kampar District. Based on the hypothesis test (Significant Test), the Probability value of α is 0.05 ig sig (0.05 ≥ 0.00) which means Ha is accepted and Ho is rejected. Thus it can be denied that emotional intelligence is approved of adolescent behavior.